2004
DOI: 10.1534/genetics.104.026682
|View full text |Cite
|
Sign up to set email alerts
|

Insertions of Mini-Tn10 Transposon T-POP in Salmonella enterica sv. typhi

Abstract: We have mutagenized a clinical strain of Salmonella enterica sv. typhi with mini-transposon Tn10dTet (T-POP) to obtain conditional lethal (tetracycline-dependent) mutants with T-POP insertions upstream of essential genes. Generalized transducing phage P22 was used to introduce T-POP from a S. typhimurium donor into a S. typhi recipient. Chromosomal DNA was purified from the mutagenized donor strains, fragmented, and then electroporated into S. typhi to backcross the original T-POP insertions. Four tetracycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(1 reference statement)
1
14
0
Order By: Relevance
“…This new family of putative HJRs is typified by E. coli YqgF protein. The yqgF gene is highly conserved among bacterial genomes (Aravind et al ., ; Ponting, ) and, unlike RuvC, is essential for growth of many bacteria, including E. coli (Freiberg et al ., ), Mycobacterium tuberculosis (Sassetti et al ., ), and Salmonella enterica serovar typhimurium (Hidalgo et al ., ). Various studies have found notable structural similarities in the folds of E. coli RuvC and YqgF proteins (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 97%
“…This new family of putative HJRs is typified by E. coli YqgF protein. The yqgF gene is highly conserved among bacterial genomes (Aravind et al ., ; Ponting, ) and, unlike RuvC, is essential for growth of many bacteria, including E. coli (Freiberg et al ., ), Mycobacterium tuberculosis (Sassetti et al ., ), and Salmonella enterica serovar typhimurium (Hidalgo et al ., ). Various studies have found notable structural similarities in the folds of E. coli RuvC and YqgF proteins (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 97%
“…An alternative approach was published in 2004 (based on previously developed techniques) to identify larger numbers of essential genes, by insertion of conditional lethal mutations into random gene fragments in a S. typhimurium strain [7]. The conditional switch used here was growth temperature, while tetracycline-dependent expression was used by others [8], although they only reported indings for four essential genes. A few years later, transposon (Tn) mutagenesis combined with high-throughput sequencing became available and this was applied to S. enterica strains [9][10][11][12].…”
Section: Essential Genes Based On Published Gene Inactivation Studiesmentioning
confidence: 99%
“…Exposure to low pH has also been tested [8]. Moreover, even 'essential' genes can often endure a transposon insertion without complete loss of function.…”
Section: Essential Genes Based On Published Gene Inactivation Studiesmentioning
confidence: 99%
“…In an attempt to make use of these properties, a Tn10-based system was developed previously (28); however, this transposon has the disadvantage of nonrandom insertion, leading to mutational hotspots (1). Furthermore, a Tn10 variant in which the tetracycline resistance gene tetA was present has been employed (20)(21)(22). As a result, tetracycline-induced transcription must proceed from P A through the resistance gene before reaching the target gene downstream of the insertion site.…”
mentioning
confidence: 99%